SISTEM INFORMASI WEB PROFIL DESA LUBUK JERING KECAMATAN AIR HITAM KABUPATEN SAROLANGUN PROVINSI JAMBI : System, Information, Profile Desa Lubuk Jering, Website - Simorangkir, Lucy; Rudi Yaman, Maman (JURNAL AKADEMIKA, 2023)
Desa Lubuk Jering is one of the villages in Air Hitam District, Sarolangun Regency, Jambi Province. Most of their lives work in the agricultural and business sectors. Recognizing the magnitude of the benefits of currently developing information technology, a web-based system is needed that aims to make it easier for the community to find information in the village at any time, without having to be limited in the working hours of village officials to obtain this information. The input needs are in the form of admin data, year data, official data, pkk data, neighborhood association data, work program data, achievement data, announcement data, activity data, and message data. Process requirements are announcement pages, activity pages and other processes, while output requirements are activity data reports and announcement data reports. With this web-based information system, village communities can more easily get information and can provide advice to the village. So that the expected results by building this system can motivate people to become more familiar with technology and take advantage of technological developments, especially for the village youth.